Let f(x) = −4x+72x−2−4x+72x−2, find f-1(x).

Status
Not open for further replies.

sarahlee

New member
Joined
Aug 25, 2018
Messages
17
Moderator Note: We have received multiple reports that this test question has been posted at four different sites (so far). This thread has been closed. We are waiting for your response to our private message.


Section 2 Functions

B]2) Let f(x) = [FONT=MathJax_Main]−[/FONT][FONT=MathJax_Main]4[/FONT][FONT=MathJax_Math-italic]x[/FONT][FONT=MathJax_Main]+[/FONT][FONT=MathJax_Main]7[/FONT][FONT=MathJax_Main]2[/FONT][FONT=MathJax_Math-italic]x[/FONT][FONT=MathJax_Main]−[/FONT][FONT=MathJax_Main]2[/FONT]−4x+72x−2, find f-1(x).
Answer: (Correct to 3 decimal places) f-1(x) = (-2 x + [/B]) / ( x + ).
 
Last edited by a moderator:
Section 2 Functions
2) Let f(x) = [FONT=MathJax_Main]−[/FONT][FONT=MathJax_Main]4[/FONT][FONT=MathJax_Math-italic]x[/FONT][FONT=MathJax_Main]+[/FONT][FONT=MathJax_Main]7[/FONT][FONT=MathJax_Main]2[/FONT][FONT=MathJax_Math-italic]x[/FONT][FONT=MathJax_Main]−[/FONT][FONT=MathJax_Main]2[/FONT]−4x+72x−2, find f-1(x).
Answer: (Correct to 3 decimal places) f-1(x) = (-2 x +
) / ( x + ).

I suspect the function is supposed to be f(x) = (−4x+7)/(2x−2), and you want to find the inverse, f-1(x), which can also be written as f^{-1}(x). This is why it's important to type the problem in yourself, not paste it, and to check the results. Note especially the importance of parentheses.

Have you learned the technique for finding an inverse? A common procedure is to write y = (−4x+7)/(2x−2), then swap variables, x = (−4y+7)/(2y−2), and then solve for y.

See what you can do. You'll probably have to ask for help at some point, if you haven't done these before. Show your work, and tell us why you are stuck.
 
Status
Not open for further replies.
Top